A Survey of the Usages of Deep Learning for Natural Language Processing - Otter, Daniel W.; Medina, Julian R.; Kalita, Jugal K. (IEEE transaction on neural networks and learning systems, 2021)
Over the last several years, the field of natural language processing has been propelled forward by an explosion in the use of deep learning models. This article provides a brief introduction to the field and a quick overview of deep learning architectures and methods. It then sifts through the plethora of recent studies and summarizes a large assortment of relevant contributions. Analyzed research areas include several core linguistic processing issues in addition to many applications of computational linguistics. A discussion of the current state of the art is then provided along with recommendations for future research in the field.